KH. SHALEH DARAT DAN KONTRIBUSINYA DALAM PENGEMBANGAN ‘ULUM AL-QUR’AN DI INDONESIA - Mukhamad Zulfa (Academic Journal of Islamic Principles and Philosophy, 2021)
Kiai Shaleh Darat was involved in the process of transmitting the knowledge of the Qur'an to Indonesian archipelago. Two of his works entitledÂ Faid al-RahmÄnin the field of Qurâ€™an interpretation andÂ Al-Mursyid Al-WajÄ«zin the field ofÂ 'UlÅ«m al-Qur'Änhave encouraged the society building especially in Central Java. However, not many religious educational institutions teach these two books.Â Al-Mursyid Al-WajÄ«zbecame the introduction to the study of Qur'an at that time as an initial study of understanding the Qur'an. He implemented a special strategy to make social change within his community:Â first, the use of Arabic Pegon script to make it easier for the public to understand and practice the teachings of Islam, wherein the Dutch East Indies government intervened in Islamic learning at the time.Â Second, he kept working as an effort to maintain the originality of Islamic knowledge during the process of transmitting knowledge from generation to generation.Â Third, Kiai Shaleh Darat positioned himself as a role model (uswah hasanah) through his productivity as an author who cares about locality. With this work, kiai Shaleh Darat contributed a lot in advancing the study of Qur'an andÂ 'UlÅ«m al-Qur'Änin archipelago with elements of locality that became his trademark.